Determination of vertical dimension using intercanthal distance in adult Mongoloid race - Yaw, Law Kam; Subrata, Gantini; Ardan, Rachman (Padjadjaran Journal of Dentistry, 2014)
Objective methods of determining the vertical dimension of occlusion (VDO) offer significant advantages because no radiographs or others special measuring devices are required. One of the objective measurement of vertical dimension of occusion is twice the intercanthal distance (ICD). The purpose of this study was to compare whether there was a difference between the length of VDO and the length of twice the ICD among Mongoloid race, which was represented by eighty students, chosen randomly from undergraduate students of Faculty of Dentistry Universitas Padjadjaran that fulfilled all criteria stated. Result showed that there was no difference between the length of VDO and twice the ICD in this population. Thus, in this study, the ICD can be suggested as a method to determine the VDO in this population.